Obesity reprograms the normal pancreas and pancreatic cancer microbiome in mice and humans - da Cruz, Raquel Santana; Suguru, Shravanthy; Paiva, Sara P. C.; Nwugwo, Ijeoma; Kallakury, Bhaskar; Weinberg, Benjamin A.; Cook, Katherine L.; de Assis, Sonia (Frontiers in Microbiomes, 2025)
IntroductionPancreatic ductal adenocarcinoma (PDAC) is an aggressive form of pancreatic cancer, with overall 5-year survival rates of about 8%. Obesity (and underlying metabolic dysfunction) is estimated to account for up to 50% of all PDACs. Microbial communities can be modulated by obesity and exert biological effects on tissues they colonize as well as distant sites. Recent studies showed that tumors, including PDAC, harbor a microbiome that is able to regulate cancer outcomes such as tumor progression, response to therapy and overall survival. Yet, it is not understood whether patient’s characteristics impact this relationship.MethodsWe examined the influence of obesity (defined by body weight in mice or body mass index [BMI] in humans) on the normal and cancerous pancreas microbiome in mice and humans using 16S sequencing.ResultsOverall, we observed that diet-induced obesity accelerated PDAC progression in the KC mouse model of PDAC. We also detected an obesity-induced decrease in the microbial abundance of the normal or cancerous pancreas. Obesity modified the bacterial community composition in the normal pancreas and PDAC of both mice and humans. Further, obese animals and humans each had a distinctive pancreatic microbiome signature with specific bacterial phylum, genus and species compared to controls. Notably, both the normal mouse pancreas and human PDAC showed an obesity-induced decrease in Pseudomonadota phylum. We also found that the presence of cancer by itself reduced microbial diversity in both the pancreas as well the intestinal microbiota. This reduction in microbial richness was further exacerbated by obesity. Finally, we observed that obesity increased inflammatory cytokines and altered the tumor immune infiltrate in humans and mice.DiscussionFurther investigation of obesity-driven microbial differences in the pancreas could provide important insights for personalized treatments for PDAC patients.